Impact of the NW-TFET Diameter on the Efficiency and the Intrinsic Voltage Gain From a Conduction Regime Perspective - Bordallo, Caio C. M.; Sivieri, Victor B.; Martino, Joao Antonio; Agopian, Paula G. D. [UNESP]; Rooyackers, Rita; Vandooren, Anne; Simoen, Eddy; Thean, Aaron Voon-Yew; Claeys, Cor (Ieee-inst Electrical Electronics Engineers Inc, 2016)
In this work, the impact of the diameter on vertical nanowire tunnel field effect transistors is analyzed focusing on the conduction mechanism and analog parameters, considering different conduction regimes. The diameter influence is investigated using experimental and simulation data. The impact of the diameter on the analog parameters is analyzed, considering both weak and strong conduction. For a smaller diameter, the impact of band-to-band tunneling (BTBT) on the device characteristics increases, showing opposite trends for weak and strong conduction. For strong conduction, a degradation of the intrinsic voltage gain occurs for very small diameters, because the device has less available area for the occurrence of tunneling. For weak conduction, the reduction of the diameter increases the BTBT along the channel/source junction without showing this degradation.
Keywords: Analog performance; band-to-band tunneling (BTBT); conduction mechanism; tunnel field effect transistor (TFET)